Disiplin Guru Dalam Melaksanakan Tugas Pembelajaran Di Masa Pandemi Covid 19 - Kastawi; Danim, Sudarwan (Manajer Pendididikan, 2023)
The purpose of the study was to describe teacher discipline in carrying out learning tasks during the Covid 19 pandemic and to find out the obstacles faced and how to overcome them. Quantitative and qualitative descriptive methods. The research population is teachers in the Talang Empat sub-district, Central Bengkulu. Collecting data using questionnaires and interviews. Quantitative data analysis techniques used descriptive statistics and qualitative data analysis according to Sugiyono. The results showed that teacher discipline in carrying out learning tasks during the covid-19 pandemic was in the moderate category. With details of teacher discipline in planning, assessment and evaluation of learning all in the medium category. Constraints found (1) from the teacher's side, many teachers do not have laptops, inadequate signals, limited knowledge and practice of using online learning platforms; (2) from the student's perspective, many students do not have an android cellphone, lack of signal, limited quota and many students who lack parental monitoring in PJJ learning. In an effort to overcome this by combining online and offline learning, schools hold workshops for teachers in the use of online learning technology, and provide internet quotas for students and teachers.